PROSEDUR PERINGATAN DINI RETENSI MAHASISWA: STUDI KASUS PENGELOLAAN INSTITUSI PERGURUAN TINGGI (SEBUAH PENELITIAN KUALITATIF) - Ade Eka Permana; Eko Budi Santoso (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study investigates factors influencing student resignation and explores the role of academic departments and study programs in implementing early warning systems at Ciputra School of Business Makassar (CSB Makassar). Using a qualitative approach, in-depth interviews with students, faculty, and administrative staff were conducted to identify financial constraints, academic dissatisfaction, and social adaptation issues as key factors affecting retention. The research highlights the importance of proactive measures such as mentoring, academic advising, and personalized interventions to address these challenges. A proposed early warning system utilizing data analytics and real-time monitoring aims to identify at-risk students and deliver timely support. The findings contribute to understanding student retention dynamics and offer practical strategies for improving institutional practices. These insights are expected to enhance student engagement and satisfaction, providing a framework for other higher education institutions facing similar challenges.